A part of the Bdelloidea and Raphignathoidea fauna (Trombidiformes: Prostigmata) in Lorestan Province, with Cyta kreiteri recorded for the first time from Iran - Maryam Khosravinejad; Shahriar Jafari; Saeid Paktinat-Saeij (Persian Journal of Acarology)
In this study, 18 species from six families were collected from Lorestan Province. Cyta kreiteri Barber & Ueckermann, 2017 was recorded for the first time from Iran.